The Praeger Handbook of Human Resource Management - Gilley, Ann (Praeger, 2012)
This is an indispensable resource for anyone with a question relating to workplace practice or policy. Volume One contains information organized by HR task or topic: Recruitment and selection, employee development, performance management, compensation and benefits administration, and employment law. Volume Two covers organizational issues like leadership and HR strategy, organizational development, change management, and general HR issues and workplace policy.